The Need for a Better Analysis of Global Prison Conditions - Sarah Dickey (Washington University Global Studies Law Review, 2022)
During the COVID-19 pandemic, I, like many others, spent a good deal of time watching various Netflix series. One remained impactful: Inside the World’s Toughest Prisons takes viewers around the globe, spending time in various prisons. The hosts found prisoners across the world are treated very differently depending upon the country in which they are incarcerated. There is a harsh dichotomy between some nations, such as Germany and Norway, where prisons seem to have adequate resources and focus on rehabilitation; and other nations, such as the Philippines and Papua New Guinea, where there is dramatic overcrowding and a lack of resources to provide enough food for all prisoners. Globally, approximately eleven million people are incarcerated: they have either been sentenced or are awaiting trial. More than half of this population is incarcerated for non-violent offenses, and half a million people are serving life sentences. Treatment in prison and prospects after prison are very different in each country. In Norway, prison cells look like college dorm rooms, while in Brazil, inmates may not have a bed. And if an individual has been incarcerated once, there is a good chance they will be incarcerated again – this is known as recidivism. Recidivism rates vary drastically: Norway has a recidivism rate of around twenty percent, while the United States has a recidivism rate of over seventy-six percent. Furthermore, responsibility for prison conditions is very different depending upon the state and the state’s authority over their own citizens. This note explores how a country’s treatment of prisoners is an indicator of its development and should be a component of the Human Development Reports. Prison conditions show the world how a State treats individuals who have committed wrongs within its borders. How a State treats their incarcerated persons indicates the extent of a State’s commitment to human rights. Currently, the Human Development Reports consider as a human security indicator only one statistic regarding inmates, which is prison population, expressed per 100,000 people. Measuring human security according to prison population has its uses, but is, however, underinclusive. There needs to be a new, separate metric: prison conditions. The creation of an entirely separate indicator for prison conditions more appropriately accounts for differences in prisoner treatment across the world and encourages all States to treat prisoners fairly.